2016
DOI: 10.1007/s00429-016-1351-5
|View full text |Cite
|
Sign up to set email alerts
|

Cortico-subthalamic inputs from the motor, limbic, and associative areas in normal and dopamine-depleted rats are not fully segregated

Abstract: The subthalamic nucleus (STN) receives monosynaptic glutamatergic afferents from different areas of the cortex, known as the "hyperdirect" pathway. The STN has been divided into three distinct subdivisions, motor, limbic, and associative parts in line with the concept of parallel information processing. The extent to which the parallel information processing coming from distinct cortical areas overlaps in the different territories of the STN is still a matter of debate and the proposed role of dopaminergic neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 53 publications
4
15
0
Order By: Relevance
“…enforces the idea that in rat territories are highly intertwined and the STN represents a site of convergence for numerous cortical projections, as suggested by former studies (42,43).…”
Section: Discussionsupporting
confidence: 83%
“…enforces the idea that in rat territories are highly intertwined and the STN represents a site of convergence for numerous cortical projections, as suggested by former studies (42,43).…”
Section: Discussionsupporting
confidence: 83%
“…These brain regions are not connected directly, but high-frequency stimulation nevertheless uncovered a high level of functional connectivity. Furthermore, electrical stimulation approaches have demonstrated that individual STN neurons receive input from motor and limbic areas53. In this way, two distinct behavioural modalities, motion and emotion, can converge, which explains some of the mixed clinical effects of DBS.…”
Section: Insights From Animal Modelsmentioning
confidence: 99%
“…The subthalamic nucleus (STN), the sole glutamatergic nucleus in the basal ganglia, is in a unique and powerful position to influence the processing of motor information. The STN receives glutamatergic inputs from multiple areas of the cortex ( Petreanu et al, 2009 ; Janssen et al, 2016 ), and is located at the crux of two primary basal ganglia pathway outputs (indirect and hyperdirect, Smith et al, 1998 ; Nambu et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%